DEVELOPMENT OF CONTEXTUAL ELKPD ASSISTED LIVEWORKSHEET ACCOMPANIED BY INTERACTIVE VIDEO IN CLASS VIII - Mufida Sari, Rika; Linuhung, Nego; Wicaksono Sudarman, Satrio (Universitas Muhammadiyah Metro, 2026)
Students still have difficulty understanding the Pythagorean Theorem because the teaching materials are not interesting, have not provided concrete examples, and have not made optimal use of digital media. This is evidenced by the daily test scores of students where a total of 71% of students got a score below the set KKTP of 75. This study aims to produce a contextual E-LKPD assisted by a Liveworksheet accompanied by a valid and practical interactive video for grade VIII students. E-LKPD was designed using Canva, features interactive videos from YouTube, and is converted to an interactive format with Liveworksheet for easy access and online work. This study uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model with 10 students in class VIII B MTs N 1 East Lampung. The instruments used include validation sheets of material experts, media experts and student practicality questionnaires. The validation results showed a validity score of 84.75% from material experts and 87.66% from media experts, with an average of 86.2% in the very valid category. Meanwhile, the practicality results of the students were 90% with the category of very practical. Thus, this Canva and Liveworksheet-based contextual E-LKPD is declared to be very valid and very practical. This media is suitable for use as an alternative teaching material that supports interesting, flexible, and in accordance with the Independent Curriculum. Peserta didik masih mengalami kesulitan memahami Teorema Pythagoras karena bahan ajar kurang menarik, belum memberikan contoh konkret, dan belum memanfaatkan media digital secara optimal. Hal ini dibuktikan dengan nilai ulangan harian peserta didik yang dimana sejumlah 71% peserta didik mendapat nilai dibawah KKTP yang ditetapkan yaitu sebesar 75. Penelitian ini bertujuan untuk menghasilkan E-LKPD kontekstual berbantu Liveworksheet disertai video interaktif yang valid dan praktis untuk peserta didik kelas VIII. E-LKPD dirancang menggunakan Canva, dilengkapi video interaktif dari YouTube, dan diubah ke format interaktif dengan Liveworksheet agar mudah diakses dan dikerjakan secara daring. Penelitian ini menggunakan model ADDIE (Analysis, Design, Development, Implementation, Evaluation) dengan subjek 10 peserta didik kelas VIII B MTs N 1 Lampung Timur. Instrumen yang digunakan meliputi lembar validasi ahli materi, ahli media dan angket kepraktisan peserta didik. Hasil validasi menunjukkan skor kevalidan 84,75% dari ahli materi dan 87,66% dari ahli media, dengan rata-rata 86,2% dengan kategori sangat valid. Sedangkan Hasil kepraktisan dari peserta didik sebesar 90% dengan kategori sangat praktis. Dengan demikian, E-LKPD kontekstual berbasis Canva dan Liveworksheet ini dinyatakan sangat valid dan sangat praktis. Media ini layak digunakan sebagai bahan ajar alternatif yang mendukung pembelajaran matematika yang menarik, fleksibel, dan sesuai dengan Kurikulum Merdeka